Karakteristik Daerah Penangkapan dan Pengaruh Parameter Oseanografi terhadap Produksi serta Status Pemanfaatan Ikan Lemuru (Sardinella lemuru) di PPI Kedonganan, Bali - Wirastika Adhihapsari; Alren S. F. Irianto; Tri D. Lelono; Daduk Setyohadi; Eko S. Yulianto (Amanisal: Jurnal Teknologi dan Manajemen Perikanan Tangkap, 2026)
The Bali Strait (FMA 573) is a critical fishing ground and primary habitat for Bali sardinella (Sardinella lemuru), a small pelagic species under increasing exploitation pressure from traditional fishing fleets. However, studies integrating fishing ground characteristics, oceanographic influences, and exploitation status at PPI Kedonganan remain limited. This study aimed to characterize fishing grounds, assess the influence of oceanographic parameters (SST and chlorophyll-a) on fish production, and evaluate the exploitation status of S. lemuru landed at PPI Kedonganan, Bali. Data were collected from February to April 2025 using simple random sampling (n = 1,882 for length-weight analysis; n = 256 for sex ratio). Fishing ground characterization was conducted through participatory mapping. SST and chlorophyll-a data were obtained from Aqua MODIS satellite imagery (2020–2024) and correlated with monthly production data using Pearson correlation analysis. Exploitation status was estimated using the Length-Based Spawning Potential Ratio (LB-SPR) method. This result known that fishing grounds were concentrated within the coastal zone at 1–3 nautical miles from shore, operated by traditional vessels (<5 GT) using purse seine, gillnet, and lift net with mesh sizes of 1–1.5 inches. A weak negative correlation was found between SST and fish production (r = −0.359, p > 0.05) and a very weak positive correlation between chlorophyll-a and production (r = 0.135, p > 0.05), both governed by monsoon dynamics and upwelling. Biological parameters confirmed dominance of immature individuals: negative allometric growth (b = 2.9358; R² = 0.9297), mean condition factor K = 1.01, balanced sex ratio (1:1), and length at first capture (Lc = 13.92 cm) below length at first maturity (Lm = 17.3 cm). LB-SPR analysis yielded SPR = 6%, classifying the stock as over-exploited — a cumulative consequence of coastal fishing grounds, non-selective gear, and intensive capture of pre-spawning individuals. Management interventions are urgently needed, including minimum mesh size regulations and periodic stock monitoring through the LB-SPR approach.